2019
DOI: 10.1016/j.biopsych.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a/Death-Associated Protein Kinase 1 Signaling Induces Synucleinopathy and Dopaminergic Neuron Degeneration in Parkinson’s Disease

Abstract: BACKGROUND: Death-associated protein kinase 1 (DAPK1) is a widely distributed serine/threonine kinase that is critical for cell death in multiple neurological disorders, including Alzheimer's disease and stroke. However, little is known about the role of DAPK1 in the pathogenesis of Parkinson's disease (PD), the second most common neurodegenerative disorder. METHODS: We used Western blot and immunohistochemistry to evaluate the alteration of DAPK1. Quantitative polymerase chain reaction and fluorescence in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 40 publications
(32 reference statements)
4
74
1
Order By: Relevance
“…28 DAPK1 expression is markedly raised in MPTP-induced chronic and acute PD mice, while the DAPK1 protein levels are suppressed by miR-26a overexpression. 10 However, the mechanisms between DAPK1 and noncoding RNAs are still not unclear. Therefore, we first picked out targeting DAPK1 miRNAs through TargetScan and miRNA.org, and further RT-PCR data indicated miR-124-3p was the optimal candidate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 DAPK1 expression is markedly raised in MPTP-induced chronic and acute PD mice, while the DAPK1 protein levels are suppressed by miR-26a overexpression. 10 However, the mechanisms between DAPK1 and noncoding RNAs are still not unclear. Therefore, we first picked out targeting DAPK1 miRNAs through TargetScan and miRNA.org, and further RT-PCR data indicated miR-124-3p was the optimal candidate.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, active DAPK1 promotes α-synuclein phosphorylation, overexpression of DAPK1 results in dopaminergic neuron injury and locomotor disabilities in mice with Parkinson's disease. 10 Although the previous studies indicated that the abnormal expression of DAPK1 plays a key role in central nervous system disorders, the underlying mechanisms remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of miRNAs have emerged as biomarkers for the diagnosis and prognosis of various neurological diseases (Wang et al, ; Xie et al, ). Accumulating data imply that differential miRNA expression profiles detected by sequencing are involved in developing cognitive defects (Tang et al, ) and Parkinson's disease (Su et al, ). In this study, we identified that miR‐21‐5p mediated haemin neuroprotection by targeting DUSP8 to alleviate neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The ears were sectioned at 8 µm thickness and incubated with anti-CD4, anti-CD31, and anti-MHCII antibodies (4 ears per group), and then stained with anti-goat IgG antibodies (Alexa Fluor 488) as previously described (Su et al, 2018). All antibodies were purchased from ebioscience (San Diego, USA).…”
Section: Immunofluorescencementioning
confidence: 99%